Re-maintaining Authentic Place Identity through Continuity: Sipiso-Piso, North Sumatera - Ginting, Nurlisa; Rahman, N. Vinky; Nasution, Achmad Delianur (Environment-Behaviour Proceedings Journal, 2018)
The current research observed continuity principle in maintaining place identity of Sipiso-Piso, North Sumatera, toward supporting Toba Caldera as National Strategic Tourism Area Priority. Striving to develop geo-tourism, Toba Caldera would face environmental and social risks arising instead of generating quality of life. A mix-used approach was conducted to identify respondents’ perceptions that indicates satisfying experiences. The result showed that since Sipiso-Piso merely offers the natural resources as the main attraction, the integrated planning related to strategic management then is crucial due to the increasing number of tourists and demands from several tourists’ parties.